Unexpected or Nonsuspected?: A Rare Cause of Recovered Left Ventricular Ejection Fraction After ECMO - Pemberthy, Carolina (JACC Case Rep, 2020)
Acute heart failure represents a challenge, especially in infrequent etiologies. We present the clinical case of a young woman diagnosed with acute heart failure and cardiogenic shock. Pheocromocytoma was identified as a reversible etiology. The surgical treatment led to a complete recovery of cardiac function. (Level of Difficulty: Beginner.)